Effect of orexin-A in the arcuate nucleus on cisplatin-induced gastric side effects in rats. (June 2019) - Guo, Feifei; Xu, Luo; Gao, Shengli; Sun, Xiangrong; Zhang, Nana; Gong, Yanling
Highlights: The relative expression of prepro-orexin mRNA in the hypothalamus was reduced by cisplatin. Orexin-A altered cisplatin-induced changes to the firing rate of neurons in ARC. Orexin-A in ARC alleviated the cisplatin-induced anorexia and pica. Orexin-A improved the weakened gastric motility. These effects could be partially blocked by neuropeptide Y1 receptor antagonist. Abstract: The most common side effects of the cancer chemotherapy drug cisplatin are nausea and vomiting. These effects are heavily influenced by orexigenic and anorexigenic peptides. We explored the effects of orexin-A on the cisplatin-treated rats and a possible mechanism for its effects on cisplatin-induced side effects. Quantitative real-time PCR was used to measure the change of prepro-orexin mRNA in the hypothalamus following cisplatin treatment. The effect of orexin-A and cisplatin on the firing rate of arcuate nucleus neurons was recorded. The effect of administration of orexin-A and a neuropeptide Y1 receptor antagonist to the arcuate nucleus on food intake, pica, and gastric motility on cisplatin treated rats were also measured. The relative expression of prepro-orexin mRNA in the hypothalamus was reduced by cisplatin. Exogenous orexin-A altered cisplatin-induced changes to the neuronal firing of gastric distension-responsive neurons, alleviated the cisplatin-induced anorexia, pica and improves the weakened gastric motility in the arcuate nucleus of rats. These effects could be partially blocked by intracerebroventricular injection (i.c.v.) of a neuropeptide Y1 receptor antagonist. These results suggest that orexin-A signaling ameliorates the gastric disorder induced by cisplatin in rats, and may act through neuropeptide Y neurons in the arcuate nucleus.